Growing like India: The unequal effects of service-led growth - Tianyu Fan; Michael Peters; Fabrizio Zilibotti (Yale University, Economic Growth Center, 2023)
Structural transformation in most currently developing countries takes the form of a rapid rise in services but limited industrialization. In this paper, we propose a new methodology to structurally estimate productivity growth in service industries that circumvents the notorious difficulties in measuring quality improvements. In our theory, the expansion of the service sector is both a consequence-due to income effects-and a cause- due to productivity growth- of the development process. We estimate the model using Indian household data. We find that productivity growth in non-tradable consumer services such as retail, restaurants, or residential real estate, was an important driver of structural transformation and rising living standards between 1987 and 2011. However, the welfare gains were heavily skewed toward high-income urban dwellers.
Keywords: 330; productivity development; service sector; economic growth; structural change; India; Produktivitätsentwicklung; Dienstleistungssektor; Wirtschaftswachstum; Strukturwandel; Indien